2018
DOI: 10.12688/f1000research.13563.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autism Spectrum Disorder (ASD) among the children aged 18-36 months in a rural community of Bangladesh: A cross sectional study

Abstract: Background: Autism spectrum disorder (ASD) refers to a group of complex neurodevelopment disorders characterized by repetitive and characteristic patterns of behavior and difficulties with social communication and interaction. In Bangladesh, autism in children is a significant burden of disease. Early identification of ASD could improve quality of life. The study has explored at the prevalence of ASD among rural community children aged between 18-36 months. Methods: A cross sectional study was conducted among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 23 publications
2
40
0
3
Order By: Relevance
“…The national survey of ASD in Bangladesh conducted in 2013 reported the prevalence of ASD to be 15.5 per 10,000 children, with a higher prevalence of ASD in urban (300 per 10,000 children) than rural areas (6.8 per 10,000 children) [NCDC, RCHCIB, BMRC, 2013]. Recently, one study conducted in a rural subdistrict in Bangladesh reported that the prevalence of ASD was 7.5 per 10,000 children, indicating the prevalence of ASD may be increasing in Bangladesh than previously reported [Akhter et al, 2018]. Although the prevalence of ASD is likely to be under-reported, nonetheless the urban estimates in Bangladesh are consistent with the figures reported in high-income countries [Ferrante et al, 2015;Williams, Higgins, & Brayne, 2006;Xu, Strathearn, Liu, & Bao, 2018].…”
Section: Burden Of Asd In Bangladeshmentioning
confidence: 96%
“…The national survey of ASD in Bangladesh conducted in 2013 reported the prevalence of ASD to be 15.5 per 10,000 children, with a higher prevalence of ASD in urban (300 per 10,000 children) than rural areas (6.8 per 10,000 children) [NCDC, RCHCIB, BMRC, 2013]. Recently, one study conducted in a rural subdistrict in Bangladesh reported that the prevalence of ASD was 7.5 per 10,000 children, indicating the prevalence of ASD may be increasing in Bangladesh than previously reported [Akhter et al, 2018]. Although the prevalence of ASD is likely to be under-reported, nonetheless the urban estimates in Bangladesh are consistent with the figures reported in high-income countries [Ferrante et al, 2015;Williams, Higgins, & Brayne, 2006;Xu, Strathearn, Liu, & Bao, 2018].…”
Section: Burden Of Asd In Bangladeshmentioning
confidence: 96%
“…The global burden of autism is 7.6 per 1000 population or 1 in every 132 persons 4 . In Bangladesh, the prevalence of ASD is 0.15 to 0.8% 5,6 . Scientists have found an interaction between genetic and environmental factors in ASD 7,8 .…”
Section: Methodsmentioning
confidence: 99%
“…Akhter et al proposed a cross-sectional study in [ 53 ], where they tried to find out the early detection of Autism Spectrum Disorder (ASD) symptoms among children aged 18–36 months. This study explored a rural community of Bangladesh and was conducted among 5286 children in that rural area.…”
Section: Related Work On Mental Health Using Mobile Technologiesmentioning
confidence: 99%